Multimodalidade e leitura crítica de imagens: análise de livros didáticos de línguas estrangeiras - Santos, Francisco Roberto da Silva (2020)
Current research in Applied Linguistics shows that reading teaching cannot do without a reflection on visual and critical literacies, which requires teacher education courses to adopt a curriculum that emphasizes that aspect. In such context, this study takes a look at the reading lessons proposed by the textbook adopted in the English and Spanish classes of two undergraduate courses in Letters. Based on Cazden et al. (1996), Kress; Van Leeuwen (2006), among others, this qualitative and interpretative research examines the didactic approach received by the images that make up the lessons of two textbook collections, namely Interchange Fourth Edition (2013) and Nuevo Ven (2003). The proposed reading exercises are analyzed as well as the didactic orientations presented by the teacher’s book. The results show that, despite the semiotic and ideological potential of those textbooks images, 57% of the lessons investigated have a null approach of visual elements, 34% have a purely exploratory approach; 9% employ a descriptive-analytical approach and 0% applies a critical-reflexive approach. In order to overcome that weakness, this study presents proposals for additional exercises based on a critical and reflexive approach to images and multimodal texts. Thus, one seeks to collaborate to promote the pedagogy of the multiliteracies in language teacher training courses